Short enantioselective synthesis of guggultetrol, a naturally occurring lipid - George, Shyla; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2010)
An enantioselective synthesis of the naturally occurring lipid, guggultetrol, is described with an overall yield of 24% starting from commercially available 1-pentadecanol in ten linear steps. The key chiral-inducing steps include a Sharpless asymmetric epoxidation of allylic alcohol and a dihydroxylation of an alpha,beta-unsaturated ester. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of key intermediate for (+)-tofacitinib through CoIII(salen)-catalyzed two stereocentered hydrolytic kinetic resolution of (Â±)-methyl-3-(oxiran-2-yl)butanoate - Kamble, Rohit B. (Synthetic Communications, 2018)
An enantiopure piperidine, a key intermediate for the synthesis of (+)-tofacitinib, has been achieved in high optical purity (98% ee) from readily available crotyl alcohol. The key steps involved is a CoIII(salen)-OAc-catalyzed two stereocentered hydrolytic kinetic resolution of (±)-methyl-3-(oxiran-2-yl)butanoate.
Keywords: enantioselective; Hydrolytic kinetic resolution; iodolactonization; γ-Butyralactone

Short enantioselective total synthesis of (+)-tofacitinib - Mane, Kishor D.; Kamble, Rohit B.; Suryavanshi, Gurunath (Tetrahedron Letters, 2021)
An enantioselective total synthesis of Tofacitinib (CP-690,550), a Janus tyrosine kinase (JAK3) specific inhibitor has been achieved from the readily available 4-piperidone. Proline catalysed hydroxylation is the key step for the synthesis of enantiopure 1-benzyl-4-methylpiperidin-3-ol. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Hydrogenation; L-proline; piperidone

Synthesis of 3 alkyl and 1,3-Bis(alkyl)indolizine amides from a-bromohydroxamates - Mane, Kishor D.; Bagwe, Sagar S.; More, Satish G.; Suryavanshi, Gurunath (Tetrahedron Letters, 2023)
A simple and catalyst-free method has been developed for the synthesis of hindered indolizine amide derivatives from functionalized alkyl bromides. The reaction of a variety of indolizine derivatives with azaoxyallyl cations generated in situ from a-bromoamides afforded a wide range of synthetically important mono- and di-alkylated indolizine amide derivatives in good to excellent yields.@2023 Elsevier Ltd. All rights reserved.
Keywords: a -Bromohydroxamates; Amides; HFIP; Indolizine